An inorganic helix in the supramolecular structure of trimethyltin diphenylarsinate, [me3sn(o2asph2)]n: a structural comparison of triorganotin arsinates and phosphinates - Silaghi-Dumitrescu, Luminita; Harsan, Eugenia; Zukerman-Schpector, Julio; Tiekink, Edward R. T. * (Academia Republicii Populare Romîne, 2016)
The crystallographic structure analysis of [Me3Sn(O2AsPh2)]n reveals supramolecular association owing to symmetric bridges between Me3Sn centres afforded by O2AsPh2 groups. The resulting polymer has a helical topology. A systematic analysis of triorganotin arsinato and phosphinato analogues indicates a role for the remote substituents on aggregations patterns.